Influence of Ce Addition on Microstructure and Corrosion Resistance of 2101 Duplex Stainless Steel. Issue 8 (19th May 2021) - Gong, Wei; Zhang, Lixiang; Zhang, Lei; Jiang, Zhouhua; Wang, Engang
Abstract : 2101 duplex stainless steel with low Ni content is developed to replace austenitic stainless steel in many corrosive environments. Herein, the effects of Ce addition on the microstructure and corrosion resistance of 2101 duplex stainless steel are studied. The electrochemical corrosion behavior of 2101 duplex stainless steel with Ce contents of 0, 0.005, and 0.020 wt% is studied in 3.5 wt% NaCl solution and 0.05 mol L −1 H2 SO4  + 0.05 mol L −1 KSCN solution at 25 °C. The situation is evaluated in 6 wt% FeCl3 solution at 35 °C. The results show that with increasing Ce content, the proportion of α phase in 2101 duplex stainless steel decreases, whereas the proportion of γ phase increases. At 0.005 wt% Ce, the two‐phase ratio is close to 1:1. Moreover, the partition coefficient ( K ) of elements gradually approaches 1 with increasing Ce, indicating a more uniform element distribution between the two phases. The electrochemical experiments in simulated seawater and acidic environments show that Ce addition gradually increases the corrosion potential and pitting resistance, leading to the formation of more stable passivation film. Abstract : Herein, the effects of the addition of Ce on the microstructure and corrosion resistance of 2101 duplex stainless steel, a key building material in many corrosive environments, are addressed. Ce increases the corrosion resistance by improving the segregation of alloy elements and converting irregular Al2 O3 and MnS inclusions into rare‐earth inclusions.